2019
DOI: 10.1093/ofid/ofz259
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal Carriage, Serotype Distribution, and Risk Factors in Children With Community-Acquired Pneumonia, 5 Years After Introduction of the 10-Valent Pneumococcal Conjugate Vaccine in Ethiopia

Abstract: Background There is a scarcity of data on pneumococcal serotypes carried by children in Ethiopia. We studied pneumococcal nasopharyngeal carriage rate, serotypes, and risk factors among children with community acquired pneumonia (CAP). Methods A prospective observational cohort study was performed in children with CAP, aged 0–15 years, in 2 pediatric emergency departments in Addis Ababa, Ethiopia. Nasopharyngeal swabs were cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
15
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 37 publications
(49 reference statements)
5
15
2
Order By: Relevance
“…At the time of this study, 68% of children had either not received PCV13 or only a single dose, which might contribute to the high detection rate. We found that immunisation with 2 or 3 doses of PCV13 was associated with lower prevalence of pneumococci thus corroborating earlier findings in Ethiopia [ 16 ] and the findings of our previous study [ 10 ] although this reduction was modest. A reducing effect of PCV13 immunisation on pneumococcal carriage has been reported and proven in several studies [ 17 ].…”
Section: Discussionsupporting
confidence: 92%
“…At the time of this study, 68% of children had either not received PCV13 or only a single dose, which might contribute to the high detection rate. We found that immunisation with 2 or 3 doses of PCV13 was associated with lower prevalence of pneumococci thus corroborating earlier findings in Ethiopia [ 16 ] and the findings of our previous study [ 10 ] although this reduction was modest. A reducing effect of PCV13 immunisation on pneumococcal carriage has been reported and proven in several studies [ 17 ].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, between 2000 and 2015 there was a 22% global decline in clinical pneumonia cases in the general children group and of 45% in the HIV-1-infected children group [12]. The 10-valent pneumococcal vaccine (PCV10) has been introduced into the national immunization program of Ethiopia with a 3-prime dose (3p+0) schedule since 2011 [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Serotypes of most of the pneumococcal isolates (except of the 17 isolates from nasopharyngeal swabs of children with non-respiratory illnesses) were previously determined and have been reported elsewhere. [18][19][20][21]…”
Section: Study Sites and Source Of Bacterial Isolatesmentioning
confidence: 99%